A novel navigation system for maxillary positioning in orthognathic surgery: Preclinical evaluation. Issue 9 (November 2015) - Lutz, Jean-Christophe; Nicolau, Stéphane; Agnus, Vincent; Bodin, Frédéric; Wilk, Astrid; Bruant-Rodier, Catherine; Rémond, Yves; Soler, Luc
Abstract: Appropriate positioning of the maxilla is critical in orthognathic surgery. As opposed to splint-based positioning, navigation systems are versatile and appropriate in assessing the vertical dimension. Bulk and disruption to the line of sight are drawbacks of optical navigation systems. Our aim was to develop and assess a novel navigation system based on electromagnetic tracking of the maxilla, including real-time registration of head movements. Since the software interface has proved to greatly influence the accuracy of the procedure, we purposely designed and evaluated an original, user-friendly interface. A sample of 12 surgeons had to navigate the phantom osteotomized maxilla to eight given target positions using the software we have developed. Time and accuracy (translational error and angular error) were compared between a conventional and a navigated session. A questionnaire provided qualitative evaluation. Our system definitely allows a reduction in variability of time and accuracy among different operators. Accuracy was improved in all surgeons (mean terror difference = 1.11 mm, mean aerror difference = 1.32°). Operative time was decreased in trainees. Therefore, they would benefit from such a system that could also serve for educational purposes. The majority of surgeons who strongly agreed that such a navigation system would prove very helpful in complex deformities, also stated that it would be helpful in everyday orthognathic procedures.